Severe acute respiratory syndrome coronavirus 2 immunoglobulin G antibody: Seroprevalence among contacts of COVID-19 cases - Om Prakash; Bhavin Solanki; Jay Kirtikumar Sheth; Mina Kadam; Sheetal Vyas; Serosurveillance Research TeamFNx01 (Wolters Kluwer Medknow Publications, 2021)
Background: Multiple serosurveillance studies have focused on the presence of antibodies against severe acute respiratory syndrome coronavirus 2 in the general population and confirmed cases. However, seroprevalence of immunoglobulin G (IgG) among contacts of confirmed cases can add further value to the scientific findings. Objectives: The objective is to estimate COVID-19 seropositivity among contacts of COVID-19 cases and to compare the seropositivity between types of contact for the assessment of differential risk and transmission dynamics. Methods: Large scale population-based serosurveillance on contacts of COVID-19 cases was carried out during the second half of August 2020 in Ahmedabad using the COVID-Kavach. The seropositivity among contacts was estimated and correlated-compared with type of contact and other demographic factors. Results: With 1268 positive for IgG antibodies from 3973 samples, the seropositivity against COVID-19 among contacts of cases in Ahmedabad was 31.92% (95% confidence interval 30.48%-33.38%). The seropositivity among family contacts was significantly higher (39.36%) as compared to other contacts (28.72%) (Z = 6.60, P < 0.01). This trend is seen across all age groups and both the sex groups. The seropositivity has increasing trend with increasing age and is significantly higher among females (35.11%) than males (28.95%) (Z = 4.16, P < 0.01). Conclusion: Seropositivity of 31.92% among contacts indicates that a large proportion of contacts have already acquired immunity on account of their contact with the case. Higher seropositivity among family contacts justifies the risk categorization and testing strategy adopted for the contacts of the cases. This also reaffirms the need for contact tracing strategy for controlling the inevitable spread of pandemic.